Short-Term Immobilization Promotes a Rapid Loss of Motor Evoked Potentials and Strength That Is Not Rescued by rTMS Treatment - Gaffney, Christopher J.; Drinkwater, Amber; Joshi, Shalmali D.; O'Hanlon, Brandon; Robinson, Abbie; Sands, Kayle-Anne; Slade, Kate; Braithwaite, Jason J.; Nuttall, Helen E. (Frontiers in Human Neuroscience, 2021)
Short-term limb immobilisation results in skeletal muscle decline, but the underlying mechanisms are incompletely understood. This study aimed to determine the neurophysiologic basis of immobilisation-induced skeletal muscle decline, and whether repetitive Transcranial Magnetic Stimulation (rTMS) could prevent any decline. Twenty-four healthy young males (20  0.5 years) underwent unilateral limb immobilisation for 72 h. Subjects were randomised between daily rTMS (n = 12) using six 20 Hz pulse trains of 1.5 seconds duration with a 60 second inter-train-interval delivered at 90% rMT, or Sham rTMS (n = 12) throughout immobilisation. Maximal grip strength, EMG activity, arm volume and composition were determined at 0 h and 72 h. Motor Evoked Potentials (MEPs) were determined daily throughout immobilisation to index motor excitability. Immobilisation induced a significant reduction in motor excitability across time (-30% at 72 h; p <0.05). The rTMS intervention increased motor excitability at 0h (+13%, p <0.05). Despite daily rTMS treatment, there was still a significant reduction in motor excitability (-31 a.u., p <0.05), loss in EMG activity (-23.5% at 72 h; p <0.05), and a loss of maximal grip strength (-22%, p <0.001) after immobilisation. Interestingly, the increase in biceps (Sham vs. rTMS) (+0.8 vs. +0.1mm, p <0.01) and posterior forearm (+0.3 vs. +0.0mm, p <0.05) skinfold thickness with immobilisation in Sham treatment was not observed following rTMS treatment. Reduced motor evoked potentials drive the loss of strength with immobilisation. rTMS cannot prevent this loss of strength but further investigation and optimisation of neuroplasticity protocols may have therapeutic benefit.